The Ahmadiyya quest for religious progress : missionizing Europe 1900-1965 - Jonker, Gerdien. (Muslim Minorities, 2016)
What happens when the idea of religious progress propels the shaping of modernity? In The Ahmadiyya Quest for Religious Progress. Missionizing Europe 1900 - 1965 Gerdien Jonker offers an account of the mission the Ahmadiyya reform movement undertook in interwar Europe. Nowadays persecuted in the Muslim world, Ahmadis appear here as the vanguard of a modern, rational Islam that met with a considerable interest. Ahmadiyya mission on the European continent attracted European 'moderns', among them Jews and Christians, theosophists and agnostics, artists and academics, liberals and Nazis. Each in their own manner, all these people strove towards modernity, and were convinced that Islam helped realizing it. Based on a wide array of sources, this book unravels the multiple layers of entanglement that arose once the missionaries and their quarry met.